Acute pancreatitis following medical abortion: Case report - Amini Hashem; Hallberg Ebba; Hallberg Pär (BMC, 2004)
Abstract Background Acute pancreatitis rarely complicates pregnancy. Although most pregnant women with acute pancreatitis have associated gallstones, less common causes such as drugs have been reported. Case presentation We report the case of a 34-year-old woman who underwent medical abortion with mifepristone and gemeprost and received codeine as pain-relief during the induction of abortion. She developed a severe acute necrotizing pancreatitis which required 14 days of intensive care. Other possible etiological factors, i.e. gallstone, alcohol intake and hyperlipidemia, were excluded. Conclusions The reported case of acute pancreatitis was most likely drug-induced.